2014
DOI: 10.1155/2014/483609
|View full text |Cite
|
Sign up to set email alerts
|

Defluoridation with Locally Produced Thai Bone Char

Abstract: The fluoride sorption ability of a locally available bone char is quantified. Both a synthetic solution and natural groundwater samples from several sites are studied and compared to Indian bone char, which is widely accepted and used successfully in India and elsewhere. The Freundlich and Langmuir sorption isotherms were used to quantify sorption properties. Results show that the Thai bone char is as effective as the Indian bone char for removing fluoride from contaminated water, despite the more rigid physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…This means that uses of BBs to VNBC product have a good efficiently economic in synthesis process. In addition, the VNBC products are charred bone does not add color, taste or smell to the water which it is in line with bone char products in previous experiments [15,22,23,28,29]. This is able to help us having a confident method in VNBC synthesis, also potential applications of product in next time research.…”
Section: The Experiments On Burned Temperature Effects To + Bc Synthesissupporting
confidence: 75%
See 2 more Smart Citations
“…This means that uses of BBs to VNBC product have a good efficiently economic in synthesis process. In addition, the VNBC products are charred bone does not add color, taste or smell to the water which it is in line with bone char products in previous experiments [15,22,23,28,29]. This is able to help us having a confident method in VNBC synthesis, also potential applications of product in next time research.…”
Section: The Experiments On Burned Temperature Effects To + Bc Synthesissupporting
confidence: 75%
“…Many previous studies have been reported during the last ten years to find the low-cost, and efficient adsorbents for the removal of metal ions or color compounds in wastewater [16][17][18][19][20]. Actually, bone char has been successfully synthesized and used for fluoride removal in Tanzania and Thailand [21,22]. The effectiveness of bone char as an adsorbent has been performed using batch experiments with contained heavy metal ions and color solutions under different conditions, for example, variable pH, temperature, chemical and thermal activation, adsorbent dosage [17,18,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Langmuir adsorption capacity of 0.841-1.18 mm size, bone char was 0.243 mg/g with co-efficient value R 2 =0.984. Langmuir isotherm fitted well in comparison to Freundlich isotherm [60]. Teresaka et al (2014) studied the removal of fluoride and methylene blue (MB) by bone char prepared at different temperature range.…”
Section: Defluoridation By Bone Char and Allied Materialsmentioning
confidence: 98%
“…However, Crocus sativus and modified sludge presented the removal efficiency in the range of 80-85% when 1-10 mg/L fluoride impurities were tested [26]. A vast literature has been reported on the use of bone char for fluoride removal [27][28][29][30]. The presence of hydroxyapatite groups in bone char is effective in removing the fluoride impurities by ion exchange and electrostatic interaction mechanism.…”
Section: Langmuir and Freundlich Adsorption Isotherm Modelsmentioning
confidence: 99%